Hydrophilization of PVC surfaces by argon plasma immersion ion implantation - Bento, WCA; Honda, R. Y.; Kayama, M. E.; Schreiner, W. H.; Cruz, N. C.; Rangel, E. C. (Kluwer Academic/plenum Publ, 2003)
Commercial polyvinylchloride (PVC) sheets were treated by plasma immersion ion implantation, PIII. Samples were immersed in argon glow discharges and biased with 25 kV negative pulses. Exposure time to the bombardment plasma changed from 900 to 10,800 s. Through contact angle measurements, the effect of the exposure time on the PVC wettability was investigated. Independent of t, all samples presented contact angles, theta, equal to zero after the treatment. However, in some cases, surface hydrophilization was not stable, as revealed by the temporal evolution of theta. Samples bombarded for shorter periods recovered partially or totally the hydrophobic character while the one exposed for the longest time stayed highly hydrophilic. These modifications are ascribed to the Cl loss and O incorporation as shown by XPS measurements. Furthermore, the mobility of surface polar groups and the variation in the cross-linking degree can also affect the PVC wettability.
Keywords: PIII; PVC; wettability; plasma treatment; contact angle; XPS; roughness